(untitled) (Economic and Political Thought, 2017)
The latest financial crisis revealed not only deficiencies of the market economy systems but also of the regulatory and supervisory solutions that should at least lessen real consequences of wrong financial decisions. Normative arbitration that in the era of globalisation allows for the relocation of a company registered office to a country with fewer legal requirements led to the erosion of prudential standards. In order to counteract these tendencies, the biggest global economies established a coordination network closely linking the political aspect with the economic and financial one. The G-20 group and the Financial Stability Board (FSB) are the most important elements of that coordination process. The article aims to analyse those groups’ mutual relations. Remembering of course that original delegation for the G-20 group is from sovereign states, the author believes that they can be interpreted in terms of a scheme: principal – agent, which is known in economic and political sciences. On the other hand, the analysis of FSB activeness, with all the deficiencies resulting from incomplete subordination to the regime of international public law, indicates that it plays the role of an institution of macroprudential supervision over the global financial market. Thus, the decrease in the intensity of the systemic risk, which may still become a reality, depends on its efficient functioning. The designed mechanisms of political pressure and efficient secondary delegation to specialised supervisory groups sensu stricto make the Financial Stability Board an efficient forum implementing the tasks of macroprudential supervision.